Formulaic sequences acquisition, processing, and use (Language learning and language teaching, 2004)
Formulaic sequences (FS) are now recognized as an essential element of language use. However, research on FS has generally been limited to a focus on description, or on the place of FS in L1 acquisition. This volume opens new directions in FS research, concentrating on how FS are acquired and processed by the mind, both in the L1 and L2. The ten original studies in the volume illustrate the L2 acquisition of FS, the relationship between L1 and L2 FS, the relationship between corpus recurrence of FS and their psycholinguistic reality, the processes involved in reading FS, and pedagogical issues